Kepemimpinan Kepala Sekolah Untuk Meningkatkan Mutu Pendidikan di SMK Negeri 2 Barru (Pascasarjana UMI, 2022)
Until August 2021, the number of unemployed SMK graduates reached 11.13 percent of the total number of unemployed people in Indonesia. Principals are required to be active, creative, innovative, and productive in order to prepare their students or graduates to have academic and professional abilities in the field of competence to apply, develop, and disseminate science, technology, and art so that they can compete in DU/DI because improving the quality of education will have an impact on people's interest in choosing these schools. To obtain data, the authors use observation data, interviews, and documentation. Observations are to observe a number of school residents at SMK Negeri 2 Barru and interviews with school principals and teachers to find out the strategy and effectiveness of principal leadership in improving the quality of education at SMK Negeri 2 Barru. The results of the study concluded that the principal's strategy at SMK Negeri 2 Barru in improving the quality of education is to prepare school planning and development, improve discipline, increase graduate competence, prepare quality human resources, hold extracurricular activities and establish cooperation with school residents, committees, guardians of students, alumni, and educational institutions